Frequency and perceived influence of menopausal symptoms on training and performance in female endurance athletes - Heather M. Hamilton; Natalie M. Yarish; Kristin E. Heron (PLoS ONE, 2025)
Menopause is associated with several negative health concerns and common menopausal symptoms. Physical activity is essential to mitigate these negative effects, but menopausal symptoms may interfere with participation in physical activity. The purpose of this study was to determine the frequency and the perceived negative effect of menopausal symptoms among female endurance athletes. Female runners, cyclists, swimmers, and triathletes 40–60 years of age were recruited ( N = 187). Participants completed an online, anonymous survey that included self-reported menopausal status; the Menopausal Rating Scale (MRS), a validated measure for assessing menopausal symptoms; and the perceived effect of menopausal symptoms on training and performance. Kruskal-Wallis tests were used to examine differences in total MRS scores among participants reporting no, slight, moderate, and strong negative effects of symptoms on training and performance. The most commonly reported menopausal symptoms were sleep problems (88%), physical and mental exhaustion (83%), sexual problems (74%), anxiety (72%), irritability (68%), depressive mood (67%), weight gain (67%), hot flushes (65%), and joint and muscular discomfort (63%). The symptoms that were perceived to most negatively affect training and performance were joint and muscular discomfort, weight gain, sleep problems, and physical and mental exhaustion. Participants with a perceived strong negative effect of symptoms on training and performance demonstrated higher total MRS scores compared to participants reporting no negative effect or slight negative effect of symptoms on training and performance (p’s ≤ .001), suggesting women with more severe menopausal symptoms had a greater perceived negative effect of symptoms on training and performance. In summary, frequency of menopausal symptoms among female endurance athletes is high and severity of menopausal symptoms is similar to that reported in the general population. Despite high physical activity levels in this population, clinicians should address these symptoms to promote continued participation in physical activity.